Thulaganyo ya seretotumišo (sa Sepedi), pesalema (ya Bibele) le sefela sa kereke (ya Lutere) - Mojalefa, Mawatle J. (Verbum et ecclesia, 2025)
The structure of Sepedi traditional praise poem, a psalm (of the Bible) and a hymn (of Lutheran Church). Readers appear to recognise similarities in the structures of hymns, psalms, and ancient praise poems. This article examines whether the proposition is based on facts or truth. Similarity or difference will be realised by contrasting the strata of the three literary texts through the lens of the adapted narratological model. In the content of traditional praise poem, the poet uses the traditional events which are not extracted from his own source. When comparing psalm and hymnal content events, it is clear that they have similarities with traditional praise poem content. This is due to the fact that they are derived from the same source. Traditional praise poet recites the same topic of praising a chief, an animal or a thing, while a psalmist and a hymnist’s topics are related to praising and praying to the Lord and not a chief or a thing. In this manner, a psalmist and a hymnist agree on their structure of the topics, while a traditional praise poet differs with them. A traditional poet praise ancestors and people by paying tribute at the graveyard, whereas a psalmist or hymnist prays to God by giving sacrifices and prayers in church. This helps us understand the differences in how a hymnist, psalmist, and traditional praise poet express reverence to their God or ancestors. Intradisciplinary and/or interdisciplinary implications: This article seeks to examine two fields of study: African literary works and Biblical Study. It draws from scholars of Sepedi traditional praise poetry and sacred songs to re-read the Old Testament texts, in particular Psalms of David focusing on 2 Samuel 22:2-3 and hymnal song taken from Difela tša Kereke, ‘A re godišeng Morena’ by Paul Gerhardt.